Using patient‐reported outcome measures to improve service effectiveness for supervisors: a mixed‐methods evaluation of supervisors' attitudes and self‐efficacy after training to use outcome measures in child mental health. Issue 1 (24th January 2017) - Fullerton, Mary; Edbrooke‐Childs, Julian; Law, Duncan; Martin, Kate; Whelan, Isabelle; Wolpert, Miranda
Abstract : Background: Patient‐reported outcome measures (PROMs) are recommended by healthcare systems internationally, but there are a number of barriers to implementation. The aim of this research was to examine the impact of training supervisors in using PROMs on clinical practice, given the importance of leadership when changing behaviour. Method: Data included pre–post questionnaires from 42 supervisors, interviews after training with six supervisees and nonparticipant observations of nine video‐recorded supervision sessions. Results: After training, supervisors had more positive attitudes to administering PROMs and using feedback from PROMs and had higher levels of self‐efficacy about using PROMs in supervision. Conclusions: Findings are in line with the growing body of evidence that training child mental health staff to use PROMs may be associated with changes in attitudes, self‐efficacy and use of PROMs.